The prevalence of human T‐cell leukemia virus in blood donors in China. Issue 7 (15th April 2019) - Li, Ling; Ou, Shanhai; Huang, Chengyin; Zhou, Xueyong; Ge, Hongwei; Li, Jianping; Zeng, Jinfeng; Zhou, Alyssa; He, Liu; Xu, Quming; Wu, Jie; Li, Longhuo; et al.
Abstract : BACKGROUND: China has not yet incorporated routine human T‐lymphotropic virus (HTLV)‐1/2 blood donor screening, even though HTLV has been reported in the southeastern coastal region. This study was conducted to investigate the prevalence of HTLV in five major regions across of China. METHODS: From January 2016 to December 2017, blood samples were collected in 20 blood centers located in different regions of China. These samples were screened for HTLV‐1/2 antibodies using enzyme‐linked immunosorbent assay (ELISA). If the test samples were reactive, the samples were confirmed with a western blot (WB) assay. If the results of WB were indeterminate, the donor was interviewed after a minimum lapse of 8 weeks. All follow‐up samples from donors were tested for anti–HTLV‐1/2 with ELISA and WB. RESULTS: There were 875, 453 donor samples tested for anti–HTLV‐1/2 by ELISA. In all, 365 samples tested negative, 22 samples tested positive by WB, and 14 samples with HTLV status undetermined due to being lost to follow‐up. The prevalences were 11.09, 5.96, 3.16, 2.88 and 0.98 per 100, 000 in Xiamen, Changsha, Beijing, Shenzhen, and Nanjing blood center, respectively. The prevalences were 0 per 100, 000 for all 15 other blood centers. There was significant differences in the prevalence of HTLV in different regions of China (p = 0.0011). CONCLUSION: In China, HTLV‐1 confirmed positive donors are mainly from southeastern coastal areas. It may be necessary to conduct HTLV screening in these areas to reduce the risk of transfusion‐transmitted HTLV.